Novel 1-Bit Beam-Scanning Reflectarray With Switchable Linear, Left-Handed, or Right-Handed Circular Polarization - Hu, Jianjia; Chi, Pei-Ling; Yang, Tao (IEEE transactions on antennas and propagation, 2023)
This article proposes a novel reconfigurable reflectarray (RRA) with 1 bit beam scanning and switchable linear, left-handed (LH) circular, or right-handed (RH) circular polarization. To realize a multipolarization switchable RRA fed by a horn of arbitrarily fixed polarization, the unit cell's reflection phases in x - and y -directions are independently controlled to meet the required differential phase in each state. Explicit reflection-phase relation will be given for switching from one polarization to another while fulfilling the 1 bit beam scanning. A 10× 10 RRA was prototyped with each unit cell using only two p-i-n diodes to implement dual functions. The fabricated RRA was tested and it can experimentally demonstrate 2-D beam scanning and polarization switching among 45°/135° linear polarization and LH/RH circular polarization. In circular polarization, the measured peak gain, aperture efficiency, and 1 dB gain bandwidth are 17.2 dBic, 26%, and 8.2%, respectively. In linear polarization, the measured cross-polarization discrimination (XPD) of greater than 15 dB, peak gain of 16.8 dBi, aperture efficiency of 23.9%, and 1 dB bandwidth of 5.3% are obtained.